A Kinetic Method to Identify the Optimum Temperature for β-glucanase Activity - Venturi, F.; Andrich, G.; Quartacci, M.F.; Sanmartin, C.; Andrich, L.; Zinnai, A. (South African Journal of Enology and Viticulture, 2013)
Enzymatic preparations containing β-glucanases are largely utilised in winemaking to facilitate the filtration of musts and wines coming from grapes affected by Botrytis cinerea, and to induce the release of mannoproteins and oligosaccharides from the cell wall of yeasts. The aim of the present work was to investigate the effect of temperature on β-glucanase activity. For this purpose, the kinetic activity of a commercial enzymatic preparation containing β-glucanases was tested utilising a model solution (buffer solution of β-glucan extracted from alcoholic yeasts with a pH similar to a must/wine, with or without 13% ethanol added) at different temperatures ranging from 20 to 40°C. By an innovative procedure based on a kinetic model able to describe the time evolution of D-glucose accumulation – the final product of β-glucan hydrolysis – it was possible to relate the maximum rate of this process to temperature. The temperature at which the enzymatic activity showed the maximum value (Tmax) was close to 30°C, without any substantial variation following ethanol addition. Indeed, in spite of a remarkable reduction (of about 66%) in the catalytic activity shown by the commercial enzymatic preparation, no significant variation of the Tmax was observed, suggesting that the presence of an inhibitor such as ethanol in the reaction medium did not change the sensibility of the enzymes to temperature.